Performance analysis on grid-connected pv system during grid faults with dc-link protection and decoupled current control - Wan Nur Huda Aqilah, Alias (2021)
The advancement of technology and the increase in population have increased the demand for electrical supply as well. The drawbacks of electrical generating from nonrenewable energy to the environment have encouraged the researchers to produce clean and sustained power in vast quantities from sustainable energy. Recently, PV systems are frequently used owing to its light and easy-to-install characteristics. Although it was proven auspicious, faults can happen on the grid side of a grid-connected PV system, causing overshoot DC voltage and overcurrent. Thus, stressing the electrical component, lessening the system’s power quality and inverter’s trip. Therefore, many FRT strategies have been introduced to overcome these issues. This thesis proposed a new approach to alleviate this matter by controlling zero switching state of NPC inverter while injecting reactive current to the grid. First, the development of a two-stage grid-connected PV system was stated and the effects of grid faults were deliberated. Some conventional FRT strategies employed in the grid-connected PV system were studied. Furthermore, the efficiency of the scheme was verified by comparing it with a conventional method using DC chopper. The results showed the proposed method could lessen the overshoot DC voltage and injecting reactive current to the grid. Also, the results shown were similar to those of the conventional method.